2007
DOI: 10.1002/jcb.21597
|View full text |Cite
|
Sign up to set email alerts
|

Disease‐modifying effects of Glucosamine HCl involving regulation of metalloproteinases and chemokines activated by interleukin‐1β in human primary synovial fibroblasts

Abstract: The purpose of this study was to investigate the possible involvement of synovium in cartilage destruction in osteoarthritis (OA) patients. Using human primary synovial fibroblasts (HPSFs), we examined the effects of glucosamine (GLN) on the regulation of the expression of matrix metalloproteinases (MMP-1, -2, and -13) and chemokines (IL-8, MCP-1, and RANTES) as well as the involvement of MAPK signal pathways (JNK, ERK, and p-38) and the transcription factor of NF-kappaB on the present or absence of interleuki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
1
2

Year Published

2009
2009
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 31 publications
(19 reference statements)
1
17
1
2
Order By: Relevance
“…35 -38 Our observation about p38 MAPK activation by a 2-hour treatment with glucosamine sulfate alone that is enhanced by salt addition is in accordance with the reported induction of p38 MAPK phosphorylation in human primary synovial fi broblasts by glucosamine treatment, which is further promoted by IL-1 β . 39 Furthermore, we describe a decrease in the ERK and JNK basal and hyperosmolalityinduced phosphorylation levels stimulated by the highest concentration of the compound, when existing literature concerning these molecules' behavior in the presence of glucosamine is controversial. 2 , 4 , 12 , 32 , 39 -43 However, the phosphorylation pattern of the 3 members of the MAPK superfamily after exposure to 10 mM of glucosamine sulfate in our study could be easily justifi ed by the increased osmotic pressure measured under the particular experimental conditions.…”
Section: Discussionmentioning
confidence: 95%
“…35 -38 Our observation about p38 MAPK activation by a 2-hour treatment with glucosamine sulfate alone that is enhanced by salt addition is in accordance with the reported induction of p38 MAPK phosphorylation in human primary synovial fi broblasts by glucosamine treatment, which is further promoted by IL-1 β . 39 Furthermore, we describe a decrease in the ERK and JNK basal and hyperosmolalityinduced phosphorylation levels stimulated by the highest concentration of the compound, when existing literature concerning these molecules' behavior in the presence of glucosamine is controversial. 2 , 4 , 12 , 32 , 39 -43 However, the phosphorylation pattern of the 3 members of the MAPK superfamily after exposure to 10 mM of glucosamine sulfate in our study could be easily justifi ed by the increased osmotic pressure measured under the particular experimental conditions.…”
Section: Discussionmentioning
confidence: 95%
“…Recent research demonstrated that MMP-1 was involved in OA development in rabbit ACLT model and the amount of its expression was related with the degree of cartilage degradation . Glucosamine have a potential functions as an alternative source of MMP-1 and MMP-3 for inducing the degradation of cartilage in OA (Lu et al, 2008). Hyaluronic acid and glucosamine sulfates all can decrease the level of MMP-3 and the ratio of MMP-3/TIMP-1 in the synovial fluid in knee joints with OA (Xu et al, 2008).…”
Section: Discussionmentioning
confidence: 97%
“…We speculated that the differences maybe attribute to the different types of cells. In RASFs, AP-1 is an essential component for MMP-1 synthesis, and cooperation between mitogen-activated protein kinase (MAPK) and NF-κB signalling pathways is necessary for IL-1β-induced synthesis of MMP-1 [35]. Ren et al [36] found that cordycepin inhibited NF-κB signaling by suppressing NF-κB and IκB-α activity in Fig.…”
Section: Discussionmentioning
confidence: 99%